DETERMINASI YANG MEMPENGARUHI HARGA TANAH DI KOTA TANGERANG - Pratala, Esaka; Sugara, Asep; Supriadi , Yudi Nur (Gapenas Publisher, 2025)
This study aims to examine the influence of spatial planning policies, infrastructure, and accessibility on land prices in Tangerang City. As one of the rapidly growing urban areas, Tangerang experiences continuous shifts in land values driven by economic expansion and urban development. To address this issue, the research employs multiple linear regression analysis to measure the extent of each variable’s effect. The findings reveal that well-structured spatial planning can significantly enhance property values, while adequate infrastructure plays a vital role in strengthening the attractiveness of an area. Accessibility also emerges as a crucial factor, as locations that are easier to reach tend to have higher land prices. Overall, these three variables show strong individual as well as combined impacts on land values. The study highlights the need for consistent spatial planning, equitable infrastructure development, and improved accessibility to ensure controlled land prices while fostering sustainable economic growth and supporting sound property investment decisions.